Taxonomia de Alepia Enderlein, 1937 (Diptera, Psychodidae) e Platyplastinx Enderlein, 1937 (Diptera, Psychodidae) com ênfase nas espécies do Brasil - Lopes, Priscila Silva (2013)
Alepia Enderlein, 1937 has distribution only in the Neotropical region and so far 52 species are known, 20 of these to the Brazil. In Brazil there are registers in the Amazon region, Atlantic Forest and Caatinga from semi-arid region from Bahia, however nothing is know for other areas such as the Cerrado. Considered a genre of identification difficult due to the complex structure of the male terminalia, it was already confused with other genera of Psychodidae. Currently it is considered more closely related to Platyplastinx Enderlein, 1937. In the attempt to solve part of this problem, the present paper describes again Alepia and proposes a new diagnosis for Platyplastinx. 122 males specimes of Alepia and 8 of Platyplastinx were examined, besides of the type material of some species of Alepia deposited in the Coleção Entomológica Prof. Johann Becker do Museu de Zoologia da Universidade Estadual de Feira de Santana, Bahia, Brazil (MZFS), as well as photographs of type material from international museums. Female specimens were not examined due to difficulties in association. The specimens were treated with 10% KOH, dehydrated, and mounted in permanent slides in Canada balsam, and their structures were photographed, illustrated and characterized. All the material will be deposited in the MZFS and in the Coleção de Invertebrados do Instituto Nacional de Pesquisa da Amazônia, Amazonas, Brazil (INPA). 26 new species of Alepia and four of Platyplastinx are described. Platyplastinx obscura comb. n. is proposed. Two subgenera are created for Alepia (Xus subgen. n., Yus subgen. n.) and taxonomic comments are woven to five species of the genus (A. alcobregma Quate, 1999; A. amputonis Quate & Brown, 2004; A. distincta Bravo, Lago & Castro, 2004; A. eburna Rapp, 1945 and A. symmetrica Wagner & Hribar, 2004). A. maculipennis Bravo, Lago & Castro, 2004 is redescribed and are given three new records of Alepia to Brazil, and new records for some Brazilian states. Catalogs are also provided for the species of Alepia and of Platyplastinx, as well as identification keys to the males of these genera. With this paper, the number of known species of Alepia is elevated from 52 to 78, and of the Platyplastinx, from eight to 13.